ANCAMAN TINDAK PIDANA KEKERASAN SEKSUAL DI BALIK KENCAN ONLINE - Nanin Koeswidi Astuti (Fakultas Hukum Universitas Kristen Indonesia, 2023)
This article analyzes the threat of sex crimes behind online dating. The purpose of writing is to make the public aware that while it is easy to find friends and potential partners for a man or woman with the help of Nettitreffie, in many cases they do not avoid accusations, whether in the form of money, goods or sexual violence. . Cyber-based sexual violence (CSBE) can occur anywhere online through social media platforms and, websites and games. The TPKS Law protects experienced KSBE victims by granting representation rights at all levels of the court system and providing criminal sanctions and fines for violators.